Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Heyndrickxia coagulans LMG S-24828 Is a Safe Probiotic Strain Capable of Germinating in the Human Gut - Robin Duncan; Giacomo Mantegazza; Giorgio Gargari; Elena Pierallini; Rosario Russo; Simone Guglielmetti (Probiotics and Antimicrobial Proteins, 2025)

Simulated gastrointestinal digestion of two convenience meals using fungal enzyme formulations - Robin Duncan; Giacomo Mantegazza; Claudio Gardana; Fabio Angelini; Rosario Russo; Simone Guglielmetti (Food Bioscience, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Clover in vineyards, a potential trap plant for the mealybug Pseudococcus calceolariae—a vector of GLRaV-3 to grapevines but not clover species - Rebecca Gough; Kar Mun Chooi; Manoharie Sandanayaka; Vicky Davis; Duncan Hedderley; Tara Taylor; Daniel Cohen; Cecilia A. Prator; Rodrigo P. P. Almeida; Vaughn A. Bell; Robin M. MacDiarmid (Journal of Pest Science, 2025)
Grapevine leafroll disease (GLD) affects grapevines worldwide. The primary causal agent of GLD is grapevine leafroll-associated virus 3 (GLRaV-3), which spreads to uninfected grapevines via mealybugs and soft-scale insects. Pseudococcus calceolariae (Hemiptera: Pseudococcidae) is a mealybug vector of GLRaV-3 in New Zealand. P. calceolariae also colonizes clovers ( Trifolium spp.) growing naturally as vineyard ground cover. Separating mealybug from GLRaV-3 grapevine host could be enhanced by a trap plant: an alternative host attractive to and retentive of the target pest. We evaluated the association between P. calceolariae and ‘Grasslands Huia’ white clover (GHWC). GHWC seed was sown under grapevines in a commercial vineyard (14 × 0.4 ha plots); the control was under-vine herbicide use (7 × 0.4 ha plots, where only few Trifolium spp. plants grew). After 2 years, GHWC cover peaked at 40% mealybug infestation in 2019. From 2018 to 2021, P. calceolariae detection and abundance on GHWC was significantly higher than plants from the control plots. There was no treatment effect for mealybug infestation of grapevine leaves nor of GLRaV-3 incidence, independent of vintage. A glasshouse trial found no transmission of GLRaV-3 by P. calceolariae to any of 256 plants among five clover cultivars tested ( Trifolium spp.), including GHWC; mealybug transmitted GLRaV-3 to 35 of 107 Nicotiana benthamiana plants. The results showed that in the 5-year period, added GHWC did not decouple P. calceolariae from the grapevine to reduce GLRaV-3 incidence, but rapid colonization of GHWC by mealybug and the lack of GLRaV-3 transmission to GHWC are encouraging. Further evaluation is needed to assess whether plant biodiversity can benefit a GLRaV-3 ecological management objective.

Marine turtles as bio-indicators of plastic pollution in the eastern Mediterranean - Emily M. Duncan; Hasan Deniz Akbora; Patrizia Baldi; Damla Beton; Annette C. Broderick; Burak Ali Cicek; Charlotte Crowe-Harland; Sophie Davey; Tess DeSerisy; Wayne J. Fuller; Julia C. Haywood; Yu Jou Hsieh; et al. (Marine Pollution Bulletin, 2024)

Lactic acid bacteria naturally associated with ready-to-eat rocket salad can survive the human gastrointestinal transit - Giacomo Mantegazza; Robin Duncan; Nicolò Telesca; Giorgio Gargari; Susanna Perotti; Patrizia Riso; Simone Guglielmetti (Food Microbiology, 2024)

Use of kefir-derived lactic acid bacteria for the preparation of a fermented soy drink with increased estrogenic activity - Giacomo Mantegazza; Alessandro Dalla Via; Armando Licata; Robin Duncan; Claudio Gardana; Giorgio Gargari; Cristina Alamprese; Stefania Arioli; Valentina Taverniti; Matti Karp; Simone Guglielmetti (Food Research International, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Dietary analysis of two sympatric marine turtle species in the eastern Mediterranean - Josie L. Palmer; Damla Beton; Burak A. Çiçek; Sophie Davey; Emily M. Duncan; Wayne J. Fuller; Brendan J. Godley; Julia C. Haywood; Mehmet F. Hüseyinoğlu; Lucy C. M. Omeyer; M. Jesse Schneider; Robin T. E. Snape; et al. (Marine Biology, 2021)
Dietary studies provide key insights into threats and changes within ecosystems and subsequent impacts on focal species. Diet is particularly challenging to study within marine environments and therefore is often poorly understood. Here, we examined the diet of stranded and bycaught loggerhead ( Caretta caretta ) and green turtles ( Chelonia mydas ) in North Cyprus (35.33° N, 33.47° E) between 2011 and 2019. A total of 129 taxa were recorded in the diet of loggerhead turtles ( n = 45), which were predominantly carnivorous (on average 72.1% of dietary biomass), foraging on a large variety of invertebrates, macroalgae, seagrasses and bony fish in low frequencies. Despite this opportunistic foraging strategy, one species was particularly dominant, the sponge Chondrosia reniformis (21.5%). Consumption of this sponge decreased with increasing turtle size. A greater degree of herbivory was found in green turtles ( n = 40) which predominantly consumed seagrasses and macroalgae (88.8%) with a total of 101 taxa recorded. The most dominant species was a Lessepsian invasive seagrass, Halophila stipulacea (31.1%). This is the highest percentage recorded for this species in green turtle diet in the Mediterranean thus far. With increasing turtle size, the percentage of seagrass consumed increased with a concomitant decrease in macroalgae. Seagrass was consumed year-round. Omnivory occurred in all green turtle size classes but reduced in larger turtles (> 75 cm CCL) suggesting a slow ontogenetic dietary shift. Macroplastic ingestion was more common in green (31.6% of individuals) than loggerhead turtles (5.7%). This study provides the most complete dietary list for marine turtles in the eastern Mediterranean.

Seasonally variant low cloud adjustment over cool oceans - Youichi Kamae; Robin Chadwick; Duncan Ackerley; Mark Ringer; Tomoo Ogura (Climate Dynamics, 2019)

Successional dynamics of nitrogen fixation and forest growth in regenerating Costa Rican rainforests - Benton N. Taylor; Robin L. Chazdon; Duncan N. L. Menge (Ecology, 2019)
Regenerating tropical forests have an immense capacity to capture carbon and harbor biodiversity. The recuperation of the nitrogen cycle following disturbance can fuel biomass regeneration, but few studies have evaluated the successional dynamics of nitrogen and nitrogen inputs in tropical forests. We assessed symbiotic and asymbiotic nitrogen fixation, soil inorganic nitrogen concentrations, and tree growth in a well‐studied series of five tropical forest plots ranging from 19 yr in age to old‐growth forests. Wet‐season soil inorganic nitrogen concentrations were high in all plots, peaking in the 29‐yr‐old plot. Inputs from symbiotic nitrogen fixation declined through succession, while asymbiotic nitrogen fixation peaked in the 37‐yr‐old plot. Consequently, the dominant nitrogen fixation input switched from symbiotic fixation in the younger plots to asymbiotic fixation in the older plots. Tree growth was highest in the youngest plots and declined through succession. Interestingly, symbiotic nitrogen fixation was negatively correlated with the basal area of nitrogen‐fixing trees across our study plots, highlighting the danger in using nitrogen‐fixing trees as a proxy for rates of symbiotic nitrogen fixation. Our results demonstrate that the nitrogen cycle has largely recuperated by 19 yr following disturbance, allowing for rapid biomass regeneration at our site. This work provides important insight into the sources and dynamics of nitrogen that support growth and carbon capture in regenerating Neotropical forests.

Microplastic ingestion ubiquitous in marine turtles - Emily M. Duncan; Annette C. Broderick; Wayne J. Fuller; Tamara S. Galloway; Matthew H. Godfrey; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; Andrew G. Mayes; Lucy C. M. Omeyer; David Santillo; Robin T. E. Snape; et al. (Global Change Biology, 2019)
Despite concerns regarding the environmental impacts of microplastics, knowledge of the incidence and levels of synthetic particles in large marine vertebrates is lacking. Here, we utilize an optimized enzymatic digestion methodology, previously developed for zooplankton, to explore whether synthetic particles could be isolated from marine turtle ingesta. We report the presence of synthetic particles in every turtle subjected to investigation ( n = 102) which included individuals from all seven species of marine turtle, sampled from three ocean basins (Atlantic [ATL]: n = 30, four species; Mediterranean (MED): n = 56, two species; Pacific (PAC): n = 16, five species). Most particles ( n = 811) were fibres (ATL: 77.1% MED: 85.3% PAC: 64.8%) with blue and black being the dominant colours. In lesser quantities were fragments (ATL: 22.9%: MED: 14.7% PAC: 20.2%) and microbeads (4.8%; PAC only; to our knowledge the first isolation of microbeads from marine megavertebrates). Fourier transform infrared spectroscopy (FT‐IR) of a subsample of particles ( n = 169) showed a range of synthetic materials such as elastomers (MED: 61.2%; PAC: 3.4%), thermoplastics (ATL: 36.8%: MED: 20.7% PAC: 27.7%) and synthetic regenerated cellulosic fibres (SRCF; ATL: 63.2%: MED: 5.8% PAC: 68.9%). Synthetic particles being isolated from species occupying different trophic levels suggest the possibility of multiple ingestion pathways. These include exposure from polluted seawater and sediments and/or additional trophic transfer from contaminated prey/forage items. We assess the likelihood that microplastic ingestion presents a significant conservation problem at current levels compared to other anthropogenic threats.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

New tools to boost butterfly habitat quality in existing grass buffer strips - Robin J. Blake; Ben A. Woodcock; Duncan B. Westbury; Peter Sutton; Simon G. Potts (Journal of Insect Conservation, 2011)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.